2007
DOI: 10.1073/pnas.0705313104
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 9 is the major pathway for glycerol uptake by mouse erythrocytes, with implications for malarial virulence

Abstract: Human and rodent erythrocytes are known to be highly permeable to glycerol. Aquaglyceroporin aquaporin (AQP)3 is the major glycerol channel in human and rat erythrocytes. However, AQP3 expression has not been observed in mouse erythrocytes. Here we report the presence of an aquaglyceroporin, AQP9, in mouse erythrocytes. AQP9 levels rise as reticulocytes mature into erythrocytes and as neonatal pups develop into adult mice. Mice bearing targeted disruption of both alleles encoding AQP9 have erythrocytes that ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 28 publications
5
78
0
Order By: Relevance
“…Immunobloting with anti-rAQP3 revealed that AQP3 is abundantly 12 expressed in hRBC ( Figure 3B). In this sample the AQP3 antibody recognized a broad band at ~ 40-50 kDa, which was reduced to 29 kDa after PNGase F treatment, indicating the expression of glycosylated AQP3 in hRBC as previously described [15,26]. In bRBC two faint bands at ~ 40-50 kDa were detected.…”
Section: Aqp3 Is Not Detected In Bovine Membrane Erythrocytessupporting
confidence: 83%
See 1 more Smart Citation
“…Immunobloting with anti-rAQP3 revealed that AQP3 is abundantly 12 expressed in hRBC ( Figure 3B). In this sample the AQP3 antibody recognized a broad band at ~ 40-50 kDa, which was reduced to 29 kDa after PNGase F treatment, indicating the expression of glycosylated AQP3 in hRBC as previously described [15,26]. In bRBC two faint bands at ~ 40-50 kDa were detected.…”
Section: Aqp3 Is Not Detected In Bovine Membrane Erythrocytessupporting
confidence: 83%
“…Absence of AQP3 has also been described in mouse erythrocytes [15], where another aquaglyceroporin isoform (AQP9) plays the role of glycerol channel maintaining the red cells highly permeable to glycerol [26]. The reason why bovine red cells do not contain glycerol channels is not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis had previously been formulated for ABO and FUT2 (Greenwell 1997;Hill 2006;Casanova and Abel 2007), while in the case of GYPC, DARC, and SLC4A1 the ability of specific alleles to modulate infection susceptibility has been demonstrated for malaria (Moulds and Moulds 2000). Also, in the case of AQP3, modulation of malaria severity can be hypothesized since AQP3 represents the major channel for glycerol transport in human erythrocytes (Roudier et al 2002), and mice knockout for Aqp9, a related glycerol transporting aquaporin, display increased survival to P. berghei (Liu et al 2007). One possibility to explain the observed associations is that pathogen richness has co-varied with malaria prevalence and that nucleotide variations, even different from those previously reported to confer resistance in SLC4A1 and GYPC, affect Plasmodium entry, spread, or rosetting.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 It has previously been shown that the expression of aquaporin-9 (AQP9) changes in some pathological situations. 3,4 In this study the expression of AQP9 and its correlation with pathological grade was investigated in 100 human brain astrocytic tumours.…”
Section: Introductionmentioning
confidence: 99%